3D Facial Analysis in Acromegaly: Gender-Specific Features and Clinical Correlations - Guo, Xiaopeng; Meng, Tian; Huang, Jiuzuo; Wang, Xiaojun; Lian, Wei; Deng, Kan; Gao, Lu; Wang, Zihao; Xing, Bing; Long, Xiao (Frontiers in Endocrinology, 2018)
Objective: Quantitative investigations of facial changes in acromegaly are rare. A new imaging technique, three-dimensional (3D) stereophotography, can accurately quantify whole facial changes. We aimed to measure facial characteristics in acromegaly patients using 3D stereophotography, analyze gender-specific features, and explore clinical influencing factors. Design: Single-center case-control study. Methods: Thirty-nine acromegaly patients and 39 age- and gender-matched healthy subjects were prospectively enrolled. 3D stereophotography was performed, and facial lines and angles were quantified for each subject. Clinical information for each acromegaly patient was acquired. Results: The nose width, length, height and depth were longer; the upper and lower lips were thicker; the face length, face width and gonion-gnathion distances were longer; and the nasofrontal and columella-labial angles were smaller in the acromegaly patients, especially in males, than in the healthy controls, with statistical significance (p<0.05). No differences were found in the face breadth, columella-labial angle, or nose length, height or depth between the female patient and healthy control groups. The insulin-like growth factor 1 (IGF-1) levels in the acromegaly patients were linearly and positively correlated with the nose width (p=0.006) and gonion-gnathion distance (p=0.029) and linearly and negatively correlated with the nasofrontal angle (p=0.026). Conclusions: The acromegaly patients’ facial changes exhibit a unique trend, and the characteristics are not identical between genders. 3D stereophotography is an accurate and reliable tool for investigating facial characteristics. Recognizing the above facial features might be potential to assist in the early diagnosis and timely treatment of acromegaly and aid in predicting the severity of systemic complications.